Dehumanization and Loss of the Individual Agency by Societal Mechanisms in Sophie Treadwell’s Machinal (Journal of the College of Basic Education, 2024)
Sophie Treadwell is hardly treated as an expressionist dramatist with a radical creative tendency to show women's anxieties for liberty and to find their own voice in modern society. Therefore, in this paper, Sophie Treadwell’s play "Machinal" and its depiction of dehumanization, loss of the individual agency, societal mechanisms, maternity and the hospital-based childbirth are elucidated as a unique example of the expressionist art movement in literature. By focusing on the concept of "Maternal," the author explores how the protagonist's traumatic postpartum experience aligns with the contemporary concerns about childbirth, maternity, loss of the individual agency and obstetrical care. It argues that the way characters respond to the Young Woman's distress reflects a prevalent trend of disdaining women's anxieties about childbirth or attributing them to the supposed "weakness" or "nervous exhaustion" of modern women. Treadwell’s play highlights the legitimacy of women’s fears regarding childbirth while challenging the idea that mental-uplift can cure maternal anxiety. This aspect of the play is vital in providing a feminist social critique, questioning societal norms and prospects placed upon women during childbirth. Moreover, the paper emphasizes how "Machinal" extends its critique beyond maternity and childbirth to address broader issues of modern, patriarchal hierarchies and their ties to technological and dehumanization discourses. By exploring the intersection of intimate and institutional structures in the play, the researcher also reveals the effects these systems can have on women. To strengthen the arguments, the paper provides specific examples to illustrate how Treadwell portrays the characters' responses to the Young Woman's distress and the medical figures' representation.